PENGUATAN TATA KELOLA KOLABORATIF DALAM MENDUKUNG TRANSISI ENERGI BERBASIS ENERGI TERBARUKAN DI JAWA TENGAH - Romi Saputra; Mutiar Fitri Dewi; Vinda Verina KDP; Merintha Suryapuspita (Fakultas Politik Pemerintahan IPDN, 2026)
Abstract This study analyzes the strengthening of collaborative governance in supporting the renewable energy-based energy transition in Central Java Province. It examines how starting conditions, institutional design, facilitative leadership, and collaborative processes influence the effectiveness of stakeholder cooperation. This research employs a descriptive qualitative approach, focusing on the collaboration between the Energy and Mineral Resources Agency of Central Java Province and the Institute for Essential Services Reform (IESR). Data were collected through interviews, documentation, and literature review, and were analyzed using an interactive qualitative analysis model. The findings show that the collaboration between the Energy and Mineral Resources Agency of Central Java Province and IESR faced several challenges, including coordination constraints, limited human resources, and delays in implementation due to the dynamics of the regional government agenda. Nevertheless, the collaboration continued to operate relatively effectively because both parties shared a common objective of accelerating the energy transition, maintained complementary roles, and were supported by formal institutional cooperation. The Energy and Mineral Resources Agency acted as a regional government actor with policy authority and bureaucratic access, while IESR provided knowledge-based support, research, advocacy, and technical facilitation. This synergy enabled the collaborative process to continue despite implementation barriers. The findings indicate that the success of collaboration is not determined by the absence of obstacles, but by the actors’ ability to maintain commitment, adjust strategies, and develop shared learning. Accordingly, this collaboration has contributed to the formulation of more inclusive renewable energy policies, strengthened institutional commitment, and enhanced regional capacity to accelerate the renewable energy-based energy transition. This study offers practical implications for strengthening collaborative governance mechanisms in renewable energy development, particularly within the context of decentralized regional governance. Keywords: collaborative governance; stakeholder collaboration; renewable energy transition; energy policy; Central Java